PENGARUH LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI PDAM TIRTA BUKAE KABUPATEN LUWU UTARA - Aldi; DRS.Dirham, M.M; Sari Ratna Dewi S,H., M.H (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
This research aims to determine the influence of work motivation and organizational culture on employee performance at PDAM Tirta Bukae North Luwu. The study employs a quantitative method approach, and the research population consists of employees' performance at PDAM Tirta Bukae North Luwu. The sampling method used in this research is saturated sampling. A total of 78 samples were taken, but only 60 samples returned. To test the hypotheses, this research uses the simple linear regression analysis technique with the SPSS (Statistical Program for Social Science) 2023 software as the analytical tool. The research results indicate that the work environment has a positive and significant effect on employee performance.